Critical analysis of results after chimney EVAR raises cause for concern - Scali, Salvatore T. (2014)
OBJECTIVE: Chimney” techniques used to extend landing zones for endovascular aortic repair(chEVAR) have been increasingly reported; however, concerns about durability and patency remain. The purpose of this analysis was to examine mid-term outcomes of chEVAR. METHODS: All patients at the University of Florida treated with chEVAR were reviewed. Major adverse events(MAEs) were recorded and defined as any chimney stent thrombosis, type 1a endoleak in follow-up, reintervention, 30-day/in-hospital death and/or ≥ 25% decrease in estimated glomerular filtration rate after discharge. Primary end-points included chimney stent patency and freedom from MAE. Secondary end-points included complications and long-term survival. RESULTS: From 2008–2012, 41 patients[age ± standard deviation(SD); 73±8; male 66%(N=27)] were treated with a total of 76 chimney stents(renal, N=51; superior mesenteric artery, N=16 celiac artery, N=9) for a variety of indications: juxtarenal, 42%(N=17, 1 rupture); suprarenal, 17%(N=7), and thoracoabdominal aneurysm, 17%(N=7); aortic anastomotic pseudoaneurysm, 15%(N=6; 3 ruptures), type 1a endoleak after EVAR, 7%(N=3), and atheromatous disease, 2%(N=1). Two patients had a single target vessel abandoned due to cannulation failure and one had a type 1a endoleak at case completion(technical success = 93%). Intraoperative complications occurred in 7 patients(17%), including graft maldeployment with unplanned mesenteric chimney(N=2) and access vessel injury requiring repair(N=5). Major postoperative complications developed in 20%(N=8). 30-day and in-hospital mortality were 5%(N=2) and 7%(N=3), respectively. At median follow-up of 18.2(range 1.4–41.5) months, 28 of 33(85%) patients with available postoperative imaging experienced stabilization or reduction of AAA sac diameters. Nine(32%) patients developed endoleak at some point during follow-up [type 1a, 7%(N=3); type 2, 10%(N=4); indeterminate, 7%(N=3)], and one patient underwent open, surgical conversion. The estimated probability of freedom from reintervention(±standard error mean) was 96±4% at both 1 and 3 years. Primary patency of all chimney stents was 88±5% and 85±5% at 1 and 3 years, respectively. Corresponding freedom from MAEs was 83±7% and 57±10% at 1 and 3 years. The 1 and 5-year actuarial estimated survival for all patients was 85±6% and 65±8%, respectively. CONCLUSIONS: These results demonstrate that chEVAR can be completed with a high degree of success; however perioperative complications and MAEs during follow-up, including loss of chimney patency and endoleak may occur at a higher rate than previously reported. Elective use of chEVAR should be performed with caution and comparison to open and/or fenestrated EVAR is needed to determine long-term efficacy of this technique.